Penerapan Metode Servqual Untuk Menganalisa Kualitas Layanan Aplikasi Talenta di SLB-G Rawinala - Meyna Endah Lestari; Eva Zuraidah (Bulletin of Computer Science Research, 2022)
The quality of service is a priority, it is hoped that employees will make work easier so that they can meet the expectations of employees. Problems occur that the quality of service is still lacking in attendance order, absenteeism has not gone well, and not on time in attendance at SLB-G Rawinala. The research objective of measuring service quality affects the level of employee satisfaction with the Servqual method. Measurement of employee satisfaction was carried out with 50 respondents. The measurement of the level of customer satisfaction on the 5 dimensions of service quality service, namely Tangible, Reliability, Responsiveness, Assurance, and Empathy, obtained the results of the perception gap and employee expectations of 0.02. From the gaps grouped by questions with an IPA diagram (Importance Performance Analysis) with Tangible dimension results, the gap value is 0.03 modern equipment used to support services and Talent Applications in official applications, Reliability with a gap value of 0.03 includes prioritized questions, namely employee attendance in the application. running well, Responsiveness gap value of 0.05 SLB-G Rawinala improves and maintains service quality to be able to meet employee expectations, Assurance with a gap of -0.02 which is prioritized and improved makes customers feel confident using the talent attendance system, and Empathy with a gap value 0.01 Stable Internet network for the convenience of employees in using the Talent Application.